Effect of various tuning methods toward the controllability of temperature controller - Sapri, Syafiq Izzuddin (2017)
The ability of Proportional Integral Derivative (PID) controllers to compensate many industrial processes has led to their wide acceptance in industrial application. In this project, a comparison is made for different tuning methods of PID controller to improve the performance of the temperature control. The tuning method that involved in this experiment were Zeigler-Nichols, Cohen-Coon, Chien, Hrones, and Reswick, CHR (1), CHR (2), CHR (3) and CHR (4). To investigate the performance of the tuning, the process at first going through the open loop test. The objective of open loop test is to figure out the value of response rate (RR), dead time (Td) and time constants (Tc). Then the value of RR, Td, and Tc is used to calculate the optimum controller setting for every tuning method. The value of PID is used in the load disturbance test to observe the performance every tuning method. Based on the response produced for each tuning method, the most effective tuning method is CHR (1). The method has the highest settling time and rise time which means the response able achieve the set point faster than other tuning method. The rise time and settling time produced from the response is 0.833 minute and 3.333 minute respectively.